Potential Use of Education for Sustainable Development Oriented Interactive Learning Media in Biotechnology Learning: - Retno Gianti; Fenny Roshayanti; Nizaruddin; M. Syaipul Hayat; Mabrouka Younis Al-Ashlam (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
This qualitative descriptive study aims to analyse the potential use of interactive learning media (ILM) oriented towards education for sustainable development (ESD) in biotechnology subjects at Salatiga State Senior High School 2. The research subjects consisted of Year 10 students and six science teachers, with a sample size of 30 students. Data were collected through questionnaires, observations, and documentation, then analysed using the Miles and Huberman model. The results of the study confirmed the great potential for the application of this media based on four main aspects: 1. structural suitability: There is no strong connection between the teaching modules and ILM, 2. integration value: ESD values (social, economic, and environmental perspectives) were not yet integrated into the Biotechnology teaching module, 3. student response: There was high potential for media use in terms of the needs of Year 10 students, and 4. technical preparation: students demonstrated mature readiness in operating MPI devices during learning. In conclusion, ESD - oriented MPI is highly feasible and has the potential to be implemented to support more comprehensive and sustainable biotechnology learning in the school.